Normalized solutions for the p-Laplacian equation with a trapping potential - Wang, Chao; Sun, Juntao (Advances in nonlinear analysis, 2023)
In this article, we are concerned with normalized solutions for the -Laplacian equation with a trapping potential and -supercritical growth, where or The solutions correspond to critical points of the underlying energy functional subject to the -norm constraint, namely, for given When we show that such problem has a ground state with positive energy for small enough. When we show that such problem has at least two solutions both with positive energy, which one is a ground state and the other one is a high-energy solution.